(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The rapid migration of English as a Foreign Language (EFL) interactions to computer-mediated environments necessitates a critical reevaluation of pragmatic acquisition. While traditional instructional frameworks prioritize lexical and syntactic accuracy, the deployment of contextually appropriate speech acts in digital spaces remains a significant challenge for non-native speakers. This empirical study quantifies the pragmalinguistic and sociopragmatic competence of Uzbek EFL learners operating within asynchronous social media platforms. A cohort of 150 intermediate to upper-intermediate (B1-B2) students participated in the research. The methodology integrated a corpus analysis of 450 authentic digital interactions extracted from Telegram and Instagram, alongside an online Written Discourse Completion Task (WDCT) designed to elicit requests and apologies. Analytical coding adhered to the Cross-Cultural Speech Act Realization Project (CCSARP) taxonomy. The data revealed a pronounced reliance on direct, unmitigated strategies; 68.4% of digital requests utilized bare imperatives, demonstrating a severe deficit in internal lexical modification. Furthermore, while learners successfully deployed explicit Illocutionary Force Indicating Devices (IFIDs) in 82% of apology scenarios, they consistently failed to provide culturally appropriate explanations or offers of repair. The compressed syntactic affordances of digital platforms actively exacerbate negative L1 pragmatic transfer. Consequently, learners project unintended assertiveness, risking interactional friction. Integrating digital pragmatics and sociolinguistic mitigation strategies into the contemporary Uzbek ELT curriculum is fundamentally necessary to bridge the gap between structural linguistic knowledge and functional communicative success.